Indian Water in the New West - McGuire, Thomas R.; Lord, William B.; Wallace, Mary G. (University of Arizona Press, 1993)
Brings together the views of engineers, lawyers, ecologists, economists, professional mediators, federal officials, an anthropologist, and a Native American tribal leader--all either students of these processes or protagonists in them--to discuss how the legitimate claims of both Indians and non-Indians to scarce water in the West are being settled.